Factors Influencing Online Purchasing Behaviour Among Rural Customers in Bekok - Fan, Fui Yin; Atan, Siti Anisah (Research in Management of Technology and Business, 2025)
This research investigates the factors of rural customers towards online purchase behaviour in Bekok. The aim of the research is to determine the purchase behaviour of Bekok people. Another objective is to determine the relationship between delivery service, payment matter, and network connection with the online purchasing behaviour of rural customers. Online purchasing behaviour is the dependent variable. However, there are challenges affecting the research. The research hypotheses are related to research such as delivery service, payment matters, and network connection for better understanding of their opinion on using online purchasing by rural customers in Bekok. The first problem statement is that the purchasing and refund procedures of online shopping are greatly impacted by outstanding negative elements like privacy, safety of the way of payment, and reliability; the second is acknowledging customers’ difficulty to predict occurrence to the two factors is delayed delivery and order return problems; and the third is network connection conditions influence online purchasing by rural customers. This research uses quantitative methods to get the data, and the data will be analysed through the Statistical Package for the Social Sciences (SPSS). It provides practical insight for rural customers in Bekok and ensures their factors on using online purchasing. In this research, researchers gain knowledge of rural customers using online purchasing based on past studies. From the chapter, researchers know the factors in rural areas will affect the rural customers when using online.